Pseudo-Four Component Synthesis of Mono- and Di-Benzylated-1,2,3-Triazoles Derived from Aniline - Daniel Mendoza-Espinosa; Guillermo E. Negron-Silva; Leticia Lomas-Romero; Atilano Gutierrez-Carrillo; Rosa Santillán (Molecules, 2013)
The pseudo-four component click synthesis of dibenzylated 1,2,3-triazoles derived from aniline is reported. The cycloaddition of sodium azide to N-(prop-2-ynyl)-benzenamine (I) in the presence of equimolar amounts of p-substituted benzyl derivatives, yields a mixture of mono- and dibenzylated 1,2,3-triazoles. When two equivalents of the benzyl derivative are added to the multicomponent reaction, the selective preparation of the dibenzylated compounds is achieved. The reactivity of the aniline N-H bond in monobenzylated 1,2,3-triazoles was tested by treatment with one equivalent of a p-substituted benzyl chloride at 40 °C, rendering the dibenzylated derivatives quantitatively.